Alternative visions: permaculture as imaginaries of the anthropocene - Azambuja, Ricardo and Islam, Gazi; Roux-Rosier, Anahid (2018)
The current paper uses the concept of imaginaries to understand how permaculture provides alternative ways of organizing in response to the Anthropocene. We argue that imaginaries provide ways of organizing that combine ideas and concrete practices, imagining organizational alternatives by enacting new forms of collective practice. Permaculture movements, because of their combination of local, situated design practices and underlying social and political philosophies, provide an interesting case of imaginaries that make it possible to reimagine the relations between humans, non-human species and the natural environment. We identify and describe three imaginaries found in permaculture movements, conceiving of permaculture, respectively, as a technical design practice, a holistic life philosophy, and an intersectional social movement. These imaginaries open up possibilities for political and social alternatives to industrially organized agriculture, but are also at risk of various forms of ideological co-optation based on their underlying social premises. We discuss our perspective in terms of developing the concept of imaginaries in relation to organizational scholarship, particularly in contexts where fundamental relations between humans and the natural environment must be reimagined, as in the case of environmentalist organizing in response to the Anthropocene. - Reproduced.
Keywords: Agriculture; Anthropocene; Environment; Permaculture